Hubungan Self-efficacy dengan Perilaku Menyontek pada Siswa Saat Ujian di SMA Negeri 1 Kecamatan Suliki - Dzikra Atikah; Netrawati Netrawati (Departement of Mathematics Education, 2023)
Some students cheated or attempted to cheat during the exam. Cheating behavior in students during exams is caused by both internal and external factors. Self-efficacy is one of the internal factors that contribute to cheating behavior. The objective of this research was to: 1) to describe the self-efficacy of students at the SMA Negeri 1 Kecamatan Suliki. 2) to describe the behavior of students who cheat on exams at the SMA Negeri 1 Kecamatan Suliki. 3) to describe the relationship between self-efficacy and cheating behavior of students in the SMA Negeri 1 Kecamatan Suliki during exams. The descriptive correlational research method was used in this research. In this research, 236 students were chosen using the proportional stratified random sampling technique. A self-efficacy questionnaire with 28 items was used, as was a cheating behavior questionnaire on students during exams with 37 items. Descriptive analysis techniques and pearson product moment correlation techniques were used to process the research data. The research findings revealed that: 1) students at the SMA Negeri 1 Kecamatan Suliki had low overall self-efficacy at 37.55%. 2) the percentage of students who cheated during exams at the SMA Negeri 1 Kecamatan Suliki was 34.18%. 3) There was a negative correlation direction and a moderate degree of relationship between self-efficacy and cheating behavior in students during exams at the SMA Negeri 1 Kecamatan Suliki. A negative correlation had an inverse relationship, which means that the higher the self-efficacy, the lower the cheating behavior of students during exams at the SMA Negeri 1 Kecamatan Suliki, and vice versa, the lower the self-efficacy, the higher the cheating behavior of students during exams at the SMA Negeri 1 Kecamatan Suliki.